Mengeksplorasi Faktor-Faktor Penentu Berbagi Pengetahuan di Sektor Publik: Tinjaun Sistematis-PRISMA - Rizky, Fajar; Altino, Iqbal Caraka; Sensuse, Dana Indra; Lusa, Sofian; Safitri, Nadya; Elisabeth, Damayanti (AI Society & STMIK Indonesia, 2025)
Knowledge sharing (KS) plays is essential for improving organizational performance and innovation, enabling faster problem-solving and collaboration. However, in the public sector, participation in KS remains low, hindering organizational learning and development. As Indonesia adopts knowledge management systems in its public sector, challenges emerge in fostering knowledge-sharing behaviors. This study uses the systematic review method, following PRISMA 2020 guidelines, to identify key factors influencing knowledge-sharing intention (KSI) and propose solutions. Through a rigorous selection process, 20 relevant studies were analyzed, categorizing factors into individual, organizational, and technological groups. The results indicate that attitudes, perceived behavioral control, subjective norms, reward systems, and the perceived usefulness of technology have a significant impact on KSI. This study offers a comprehensive reference for future research on KS in the public sector and provides insights for policymakers to design initiatives that enhance organizational learning.